Performance of spectrogram cross-correlation in detecting right whale calls in long-term recordings from the bering sea - Munger, Lisa M.; Mellinger, David K.; Wiggins, Sean M.; Moore, Sue E.; Hildebrand, John A. (Canadian Acoustics, 2005)
We investigated the performance of spectrogram cross-correlation for automatically detecting North Pacific right whale (Eubalaena japonica) calls in long-term acoustic recordings from the southeastern Bering Sea. Data were sampled by autonomous, bottom-mounted hydrophones deployed in the southeastern Bering Sea from October 2000 through August 2002. A human analyst detected right whale calls within the first month (October 2000) of recorded data by visually examining spectrograms and by listening to recorded data; these manual detections were then compared to results of automated detection trials. Automated detection by spectrogram cross-correlation was implemented using a synthetic kernel based on the most common right whale call type. To optimize automated detection parameters, the analyst performed multiple trials on minutes-long and hour-long recordings and manually adjusted detection parameters between trials. A single set of optimized detection parameters was used to process a week-long recording from October 2000. The automated detector trials resulted in increasing proportions of false and missed detections with increasing data set duration, due to the higher proportion of acoustic noise and lower overall call rates in longer recordings. However, the automated detector missed only one calling "bout" (2 or more calls within a 10-minute span) of the 18 bouts present in the week-long recording. Despite the high number of false detections and missed individual calls, spectrogram cross-correlation was useful to guide a human analyst to sections of data with potential right whale calling bouts. Upon reviewing automatic detection events, the analyst could quickly dismiss false detections and search recordings before and after correct detections to find missed calls, thus improving the efficiency of searching for a small number of calls in long-term (months- to years-long) recordings.